Daily English Quotes: Meningkatkan Kepercayaan Diri dan Speaking Skill Siswa Kecantikan SMK Negeri 3 Palangka Raya - Sumarni Sumarni; Sabarun Sabarun (Lembaga Pengembangan Kinerja Dosen, 2025)
The Daily English Quotes program was implemented to enhance the self-confidence and speaking skills of Beauty Department students at SMK Negeri 3 Palangka Raya. This activity was carried out at the end of each English lesson, where two students took turns reading inspirational English quotes aloud. Afterward, the teacher provided constructive feedback related to pronunciation, meaning, intonation, and the moral values contained in the quotes. The study applied a qualitative descriptive approach involving observation, interviews, and student reflections. The findings revealed notable improvements in students’ participation, pronunciation accuracy, fluency, and self-confidence in speaking English. The classroom atmosphere became more communicative, enjoyable, and supportive, allowing students to express themselves more freely without fear of making mistakes. Based on data from 45 students, 80% showed increased participation, 76% reported higher confidence, and 72% demonstrated better fluency. Therefore, the Daily English Quotes program proved to be an effective and sustainable strategy for fostering motivation, positive character, and communicative competence among vocational students.